Perinatal outcome after planned vaginal delivery in monochorionic compared with dichorionic twin pregnancy. (2nd February 2021) - Schmitz, T.; Korb, D.; Azria, E.; Garabédian, C.; Rozenberg, P.; Sénat, M. V.; Sentilhes, L.; Vayssière, C.; Winer, N.; Goffinet, F.; ,
ABSTRACT: Objective: To assess, according to chorionicity, the perinatal outcome of twin pregnancy in which vaginal delivery is planned. Methods: JUMODA (JUmeaux MODe d'Accouchement) was a national prospective population‐based cohort study of twin pregnancies, delivered in 176 maternity units in France, from February 2014 to March 2015. In this planned secondary analysis, we assessed, according to chorionicity, the perinatal outcome of twin pregnancies, in which vaginal delivery was planned, that delivered at or after 32 weeks of gestation with the first twin in cephalic presentation. In order to select a population with well‐recognized indications for planned vaginal delivery, we applied the same exclusion criteria as those in the Twin Birth Study, an international randomized trial. Monochorionic twin pregnancies with twin‐to‐twin transfusion syndrome or twin anemia–polycythemia sequence were defined as complicated and were excluded. The primary outcome was a composite of intrapartum mortality and neonatal morbidity and mortality. Multivariable logistic regression models were used to control for potential confounders. Subgroup analyses were conducted according to birth order (first or second twin) and gestational age at delivery (< 37 or ≥ 37 weeks of gestation). Results: Among 3873 twin pregnancies, in which vaginal delivery was planned, that delivered at ≥ 32 weeks' gestation with the first twin in cephalic presentation, meeting the inclusion criteria of the Twin Birth Study, 729 (18.8%) were uncomplicated monochorionic twin pregnancies and 3144 (81.2%) were dichorionic twin pregnancies. The rate of composite intrapartum mortality and neonatal morbidity and mortality did not differ between uncomplicated monochorionic (27/1458 (1.9%)) and dichorionic (107/6288 (1.7%)) twin pregnancies when adjusting for conception by assisted reproductive technologies (adjusted relative risk, 1.07 (95% CI, 0.66–1.75)). No significant difference in the primary outcome was found between the groups on subgroup analyses according to birth order and gestational age at delivery. Conclusion: When vaginal delivery is planned, and delivery occurs at ≥ 32 weeks of gestation with the first twin in cephalic presentation, uncomplicated monochorionic twin pregnancy is not associated with a higher rate of composite intrapartum mortality and neonatal morbidity and mortality compared with dichorionic twin pregnancy. © 2020 International Society of Ultrasound in Obstetrics and Gynecology Abstract : A video abstract of this article is available online here . This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Resultado perinatal tras un parto vaginal planificado en un embarazo de gemelos monocoriónico comparado con uno dicoriónico Objetivo: Evaluar, en función de la corionicidad, el resultado perinatal del embarazo de gemelos en el que se planifica un parto vaginal. Métodos: JUMODA (JUmeaux MODe d'Accouchement) fue un estudio de cohorte nacional prospectivo basado en una población de embarazos de gemelos, nacidos en 176 unidades de maternidad en Francia entre febrero de 2014 y marzo de 2015. En este análisis secundario planificado, se evaluó, según la corionicidad, el resultado perinatal de los embarazos de gemelos, en los que estaba planificado el parto vaginal, que dieron a luz a las 32 semanas de gestación o posteriormente, con el primer gemelo en presentación cefálica. Para seleccionar una población con indicadores bien reconocidos para el parto vaginal planificado, se aplicaron los mismos criterios de exclusión que los del Twin Birth Study, un ensayo aleatorizado internacional. Los embarazos de gemelos monocoriónicos con síndrome de transfusión feto‐fetal, o con secuencia de anemia‐policitemia en los gemelos, se definieron como complicados y se excluyeron. El resultado primario fue un compuesto de la mortalidad durante el parto y la morbilidad y mortalidad neonatales. Se utilizaron modelos de regresión logística multivariante para controlar los posibles factores de confusión. Se realizaron análisis de subgrupos de acuerdo con el orden de nacimiento (primer o segundo gemelo) y la edad gestacional en el momento del parto (<37 o ≥37 semanas de gestación). Resultados: Entre los 3.873 embarazos de gemelos en los que se planificó el parto vaginal, que dieron a luz a las ≥32 semanas de gestación con el primer gemelo en presentación cefálica, y que cumplían los criterios de inclusión del Estudio sobre el Nacimiento de Gemelos, 729 (18, 8%) fueron embarazos sin complicaciones de gemelos monocoriónicos y 3.144 (81, 2%) fueron embarazos de gemelos dicoriónicos. La tasa de mortalidad compuesta durante el parto y de la morbilidad y mortalidad neonatales no difirió entre los embarazos de gemelos monocoriónicos no complicados (27/1458 [1, 9%]) y los dicoriónicos (107/6288 [1, 7%]) cuando se hicieron ajustes respecto a la concepción mediante tecnologías de reproducción asistida (riesgo relativo ajustado; 1, 07 [IC 95%, 0, 66–1, 75]). No se encontraron diferencias significativas en el resultado primario entre los grupos en los análisis de subgrupos de acuerdo con el orden de nacimiento y la edad gestacional en el momento del parto. Conclusión: Cuando se planifica el parto vaginal, y el parto se produce a las ≥32 semanas de gestación con el primer gemelo en presentación cefálica, el embarazo de gemelos monocoriónico sin complicaciones no se asocia con una mayor tasa compuesta de la mortalidad durante el parto y la morbilidad y mortalidad neonatales, en comparación con el embarazo de gemelos dicoriónico. © 2020 International Society of Ultrasound in Obstetrics and Gynecology. 摘要: 单绒毛双胎与双绒毛双胎妊娠计划分娩后的围产期预后比较 根据绒毛膜性来评估经产道计划生产的围产期预后 原理: JUMODA(JUmeaux MODe d'Accouchement)是一项基于全国人群的双胎妊娠前瞻性队列研究，该研究收集了于2014年2月至2015年3月间在法国产房分娩的176个产妇的数据 。在此计划的二级分析中，我们根据绒毛膜性进行了评估双胎妊娠的围产期预后，产妇都是按计划进行产道分娩，在妊娠32周时或之后，首次双胞胎头位分娩。为了选择公认计划阴道分娩的适应症人群，我们采用了与国际随机试验"双胞胎研究"中相同的排除标准。具有双胎输血综合征或输血症候群的单绒毛双胎被定义为疑难病且被排除。主要预后是产时死亡率，新生儿发病率和死亡率的综合利率。多变量逻辑回归模型用来控制潜在的干扰因素。根据出生顺序(第一个或第二个双胞胎)和孕周胎龄进行亚组分析。 分娩(妊娠<37或≥37周)。 结果: 在计划中分娩的3873例双胞胎妊娠中，孕期≥32周的双胞胎 第一胎头位的，符合"双胞胎出生研究"的纳入标准，其中729例(18.8%)为非疑难性单绒毛双胎妊娠，而3144例为双绒毛(81.2%)双胎妊娠。 当通过辅助生殖技术进行受孕调整时，非疑难性单绒毛膜双胎(27/1458(1.9%))和双绒毛膜双胞胎(107/6288(1.7%)在分娩死亡率和新生儿发病率的综合比率与死亡率没有差异。 调整的相对风险为1.07(95%置信区间，0.66‐1.75)。 在根据出生顺序和产位进行亚族分析时，主要预后在这些对比组之间无明显差异。 结论: 如果计划进行产道分娩，并且分娩发生在妊娠≥32周且双胞胎的第一胎出生时为头位的情况下， 则与双绒毛膜双胎妊娠相比，非疑难性单绒毛膜双胎妊娠与更高的产时死亡率，新生儿发病率和死亡率综合比率没有相关性。 ©2020国际妇产科超声学会。